(untitled) (Comparatismi, 2017)
The American Modernist poet Conrad Aiken attempted not only a thematic rapprochement with music, but also what is usually described as ‘musicalization of fiction,’ that is to say a more formal type of intermediality. By this token, Aiken occupies a specific place in literary history as an author of formal musical borrowings. Yet, paradoxically, Aiken’s use of music remains rather conventional, or traditionalist, so that it only reinforces his marginality within the Modernist world. While Harold Bloom describes Aiken’s poetry as attached to the “tradition of High romanticism”, I would willingly describe his use of music as an orthodox musical mythography, whereby the crossing of the boundaries between the arts becomes a mere poetic tool, and quite a hackneyed intersemiotic translation. In other words, far from constituting a novelty, intermediality and intersemiotic translatation are signs of an attachment to traditionalist values. Aiken’s musical singularity also appears in his novels which seem to have been initially conceived of as purely profitable projects, aiming to improve the poet’s income. However, to an extent, Aiken’s novels reflect his poetry, building on his intersemiotic poetic statements. Indeed, what comes to the fore, in both Aiken’s poetry and his novels, is an almost obsessive questioning of consciousness. And, it is music that plays a heuristic function accompanying images of consciousness. In order to demonstrate Aiken’s attachment to musical borrowings and his paradoxically traditionalist approach to intersemioticity, I will first focus on his poetic manifestos. Second, I shall concentrate on Aiken’s musical representations of consciousness, especially in his novel Blue Voyage (1927). Finally, I will refer to Aiken’s novels in relation to his vision of time as an aesthetic construct in keeping with music.